Inovasi Layanan Digital Pada Perpustakaan Daerah Provinsi Kalimantan Barat - Anny Riwayati; Annisa Rizqa Alamri (Journal on Education, 2024)
Libraries have a very strategic role for the progress of a nation. The image of a library in everyone's mind must be a book. As this book is a window of knowledge. Sometimes people feel lazy to come to the library because there is no time, but with the sophistication of technology now, the library can simply be enjoyed in the grasp of everyone's smartphone. The downside now is that many books are not available in the library, which is a boomerang for people to enjoy. They rely more on Google to get the information they want to know. West Kalimantan is the third largest region in Indonesia. People in West Kalimantan still do not have a penchant for reading books, as there are still few who visit regional libraries. Based on the Human Development Index (HDI), West Kalimantan continues to increase every year but is still in the medium category. The method used in this research is using Qualitative methods with a descriptive approach and determining informants for more in-depth results. The result of this research is that the West Kalimantan Regional Library has tried to develop services that facilitate administration. Starting from website development and application launching. It turns out that the implementation in the field is still constrained by the existing budget, there is still no funding to make improvements and application development. Apart from looking at administrative services, the government must revive libraries so that they can contribute to human civilisation in the country. Learning from the glory of the Baitul Hikmah library in its time, the book isa follows and adjusts what is their material to improve its human resources, as well as the ideals of a library established.